Bromoacetic acid induces neurogenic injury in the chicken brain by activating oxidative stress and NF-κB inflammatory pathway. (25th September 2022) - Liu, Jiwen; Wu, Yuting; Liu, Shuhui; Gao, Zhangshan; Fan, Wentao; Ding, Chenchen; Tang, Zhihui; Zhang, Shuo; Shi, Xizhi; Tan, Lei; Luo, Yan; Song, Suquan
Abstract: The bromoacetic acid (BAA) is one of the most teratogenic and neurotoxic disinfection byproducts. Birds take environmental water as their habitat and are inevitably affected by BAA in the environment. However, the neurotoxicity caused by BAA in birds has not been reported and the mechanism remains unclear. In this study, we chose chickens as the avian model to explore the effects of different concentrations of BAA on the brain tissues. Here, we selected the 3 μg/L dose of BAA detected in Tai Lake basin as a reference, and designed 1-, 100-, and 1000-fold of the environmental exposure dose as the experimental doses to explore the neurotoxicity of BAA in birds. Results showed that BAA increased the number of pyknotic nuclear neurons, deformed vascular sheaths, and glial cells in the brain. BAA inhibited the activity of antioxidant enzymes and the expression of antioxidant genes. With the increase of BAA concentration, the oxidative stress-responsive transcription factor NF-κB was activated. Furthermore, BAA remarkably changed the expression of lipid metabolism related genes (i.e., acc, gpat, hmgr, pparα, cpt1, and ampkα ). Importantly, BAA decreased the mRNA and protein expression levels of autophagy-related genes (i.e., atg5, ulk1, beclin1, and lc3 ). Meantime, BAA increased the mRNA and protein levels of apoptotic and pro-apoptotic genes, such as p53, bax, cytochrome c, caspase-9, and caspase-3 . Overall, our study provided new insights into the potential neurotoxic effects of BAA in birds, which was important for the clinical monitoring and prevention of BAA. Highlights: BAA induced neurogenic injury in the chicken brain. BAA caused oxidative stress and activated NF-κB inflammatory pathways. BAA disturbed neuronal energy metabolism and lipid metabolism in the brain. BAA inhibited autophagy in the chicken brain. BAA resulted in apoptosis in the chicken brain.